PENGARUH ULASAN DAN RATING TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN GENERASI Z PADA PRODUK KOSMETIK WARDAH DI SHOPEE (STUDI KASUS PADA MAHASISWA UNIVERSITAS MUHAMMADIYAH KUDUS PROGAM STUDI BISNIS DIGITAL) - Adila Nuril Maziyyah; Avira Budianita; Darsin Darsin (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2026)
This research was conducted based on current technological developments, particularly in e-commerce, which can influence Generation Z consumer behavior in making purchasing decisions. On the Shopee platform, reviews and ratings are also a source of information for Generation Z because they provide an overview of the experiences of previous consumers who have made purchases. Wardah cosmetic products were chosen as the object of this research because Wardah is a local halal brand that is in high demand and has high sales on Shopee. This study aims to determine the influence of reviews and ratings on Generation Z consumer purchasing decisions for Wardah cosmetic products on Shopee, with a case study of students from the Digital Business Study Program at the University of Muhammadiyah Kudus. This study uses a quantitative method with an associative approach. Data collection was carried out through distributing online questionnaires to 60 respondents selected using a purposive sampling technique. The data obtained were then analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM) with the help of SmartPLS software. The results of the study indicate that reviews and ratings have a positive and significant effect on Generation Z consumer purchasing decisions because they can increase consumer trust and encourage purchases.